In vitro activity of Benzimidazoles: oxfendazole, fenbendazole, albendazole and thiabendazole in goat gastrointestinal nematodes - Vieira, Luiz da Silva; Gonçalves, Pedro Cabral; Costa, Carlos Alberto Fagonde; Berne, Maria Elizabeth Aires (Pesquisa Agropecuaria Brasileira, 2014)
This study was carried out to determine and to compare the "in vitro" activity of the benzimidazoles: oxfendazole, fenbendazole, albendazole and thiabendazole on caprine gastrointestinal nematodes. Fecal cultures were performed and treated with benzimidazole anthelminths using five different concentrations: 6.25, 12.5, 25.0, 50.0 and 100.0 ppm. Five fecal cultures were prepared for each concentration, using distilled water in the control cultures. Thiabendazole and albendazole, showed the highest reduction percentage of infective larvae of Haemonchus, Strongyloides and of free living females of Stongyloides. Oxfendazole ranked in an intermediate position, and fenbendazole had the lowest efficacy. Against the infective larvae of Trichostrongylus, oxfendazole, albendazole and thiabendazole had efficacy higher than 95%, whereas fenbendazole was lower 95.0%. Infective larvae of Oesophagostomum were reduced by all four benzimidazoles tested with efficiencies above 96%.